Pengaruh Work-life Balance yang di Mediasi oleh Job Satisfaction terhadap Turnover Intention - Yuliani; Ekhsan, Muhamad (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2024)
This study analyzes employee work-life balance on exit intention mediated by job satisfaction of PT EPS Indonesia employees. Sampling consisted of 80 individuals, using the Slovin formula. The results show that maintaining a balance between personal and work life has a significant positive impact on the level of job satisfaction. The desire to leave a job is influenced by job satisfaction. If you have a good work-life balance, you may be happier with your job and less willing to quit. However, it does not significantly affect your desire to quit. Although some theories suggest work-life balance can increase job satisfaction and reduce resignation intention, there is inconsistency in explaining the mechanism of the relationship between these variables. This study fills the theoretical and empirical gap by analyzing the indirect effect of work-life balance on resignation intention through job satisfaction in the Indonesian corporate context. The research findings can enrich the HRM and organizational behavior literature and provide insights for companies in crafting work-life balance policies to increase job satisfaction and retain quality employees.